Efficacy of Azoles Antifungals in Treatment of Pityriasis Versicolor - Jha, Smita (Journal of Nepalgunj Medical College, 2022)
Introduction: Pityriasis versicolor is superficial fungal infection. Topical drugs are often effective in treatment of limited disease while systemic drugs are more suitable in extensive cases. The systemic triazole drugs, itraconazole and fluconazole have shown promising results at different doses. Aims: To assess the efficacy and safety of oral fluconazole combined with ketoconazole shampoo and oral itraconazole in the treatment of Pityriasis versicolor. Methods: The study was conducted at department of Dermatology at Nepalgunj Medical College from March 2019 to February 2020. Total 100 patients of both genders with Pityriasis versicolor were randomly allocated into two groups with 50 patients in each group. Patients in Group I received oral fluconazole 300mg a week for two consecutive weeks along with ketoconazole 2% shampoo twice weekly for two weeks while those in Group II received itraconazole 200mg daily for one week. Efficacy was assessed in terms of negative fungal hyphae. The drug is considered safe if no patients were withdrawn for clinical adverse effects or laboratory abnormalities. Results: In this study age ranged from 18 to 50 years with mean age of 31.1 years in Group I and 31.92 years in Group II. Efficacy was seen in 78% of Group I patients as compared to 54% in Group II patients at two weeks and 94% in Group I and 90% in Group II at four weeks. No significant adverse effects were reported in any of the group. Conclusion: Fluconazole along with ketoconazole shampoo is more effective than itraconazole in treatment of pityriasis versicolor with minimal side effects, at lesser cost.